Timing, Management, and Outcomes of Liver Transplantation in Primary Sclerosing Cholangitis - Martin, Eric F.; Levy, Cynthia (Seminars in Liver Disease, 2017)
Primary sclerosing cholangitis (PSC) is a chronic, immune-mediated cholestatic liver disease that often progresses to secondary biliary cirrhosis and end-stage liver disease. Short of liver transplantation (LT), there is no effective treatment for PSC. PSC accounts for approximately 5% of total adult LTs in the US and is currently the fifth most common indication for LT. Patient and graft survival for PSC is among the highest for all indications for LT. The main factors that impact outcomes after LT for PSC include biliary strictures, rejection, and recurrence of PSC. Recurrent PSC (rPSC) develops in 20% of LT recipients within 5 years of LT and is associated with negative patient and graft survival. LT is a viable option for recipients who develop rPSC and progress to graft failure.
Keywords: primary sclerosing cholangitis; liver transplantation; recurrence; outcomes